2016
DOI: 10.18632/oncotarget.9936
|View full text |Cite
|
Sign up to set email alerts
|

Onco-miR-130 promotes cell proliferation and migration by targeting TGFβR2 in gastric cancer

Abstract: MicroRNAs (miRNAs) have been proved to play crucial roles in tumorigenesis. TGFβ signal pathway abnormality is found in various cancers and correlates with tumor proliferation and metastasis. However, the mechanisms underlying the dys-regulation of TGFβR2 expression in GC have not been investigated yet. In this study, we found that the TGFβR2 protein was clearly repressed in tumor tissues, while miR-130 expression level was dramatically increased in GC tissues. Firefly luciferase activity assay revealed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 36 publications
4
42
1
Order By: Relevance
“…For instance, miR-23b could function as a tumor suppressor that present downregulation in stomach cancer (35) and bladder cancer (36). Whereas the miR-130 family have been identified as upregulated in many cancer types that representing putative oncogene (37,38). This pan-cancer wide meta-profiling analysis indicated that the comprehensive investigation of the database may help to illuminate the complicated relationship between miRNAs and cancers and develop more effective treatment strategies for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-23b could function as a tumor suppressor that present downregulation in stomach cancer (35) and bladder cancer (36). Whereas the miR-130 family have been identified as upregulated in many cancer types that representing putative oncogene (37,38). This pan-cancer wide meta-profiling analysis indicated that the comprehensive investigation of the database may help to illuminate the complicated relationship between miRNAs and cancers and develop more effective treatment strategies for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Wei H and colleagues found that miR-130a as an oncogenic miRNA that targets PTEN to drive malignant cell survival and tumor growth [45]. Additionally, miR130a was reported as an oncogene by directly targeting TGFβR2 in gastric cancer [46]. The expression level and biological functions of miR-130a-3p in glioma remains unclear yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, miRNAs have been demonstrated to be functionally involved in the regulation of a series of physiological and pathological processes, including cell proliferation, apoptosis, differentiation and invasion (9). Alterations in the expression of miRNAs have been widely reported in almost all types of cancer, including hepatocellular carcinoma (10), cervical (11), thyroid (12), colorectal (13) and gastric cancer (14). Previous studies have demonstrated that expression levels of miRNAs are associated with cancer initiation and progression (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%